Reperfusion injury to ischemic medullary brain nuclei after stopping continuous positive airway pressure-induced CO2-reduced vasoconstriction in sleep apnea - Jaster, J. Howard (Journal of Thoracic Disease, 2018)
The Journal recently published two papers (1,2), which described from different perspectives the physiological consequences of withdrawing continuous positive airway pressure (CPAP) from sleep apnea patients—both papers ignoring the medullary brain ischemia which results from untreated sleep apnea, and which is exacerbated by CPAP therapy, and which is further provoked by CPAP withdrawal, and which probably becomes an etiological focus for cardiac arrhythmias and sudden death. An experimental model involving withdrawal of CPAP from sleep apnea patients may therefore have inherent dangers.